Propagation In Vitro of Sorgum in MS, VW and NT mediums - Dwie Retno Suryaningsih; Sri Arijanti Prakoeswa; Maria ME (Agricultural Science, 2018)
Sorgum is one kind of plant from the family of grass in the Tropical and Subtropical regions. Sorgum bicolor is a species commonly used for molase, syrup and seeds productions. Furthermore, sorgum is also used as a biofuel material. The purpose of this research is to investigate which type of medium is best for the growth and development of sorgum explants. This research were implemented by using the Complete Random Design with 3 mediums treatment: M1 = Murashige and Skoog; M2 = Vacin and Went; and M3 = Nagata and Takabe. Repititions were done 9 times and each were using 10 test samples. Changes observed were of: qualities, quantities, and contents of phenol in the Sorgum calluses.The results of this research were:quantity of callus in general had shown real differences and most callus found were on the MS medium treatment;quality of callus formed had shown real differences in each mediums and tended to be compact callus, while in MS medium to become friable;NT medium tended to produce most contents of phenol, which was 0.25% .